Use of antenatal care services among extremely marginalized indigenous population (Chepang Community) of Nepal. - Manita Bartaula; Manish Bartaula; Nishchal Devkota (PLOS Global Public Health)
In Nepal, marginalized communities like the Chepang, who face socio-economic challenges, have limited access to healthcare services, resulting in low utilization of antenatal care (ANC) despite the availability of free maternal healthcare services. This study used a cross-sectional design using semi-structured questionnaires and in-person interviews to find out the factors influencing the use of ANC services among 130 women from Chepang (an extremely marginalized ethnic tribe) community in Rapti Municipality, Chitwan, Nepal. The collected data were entered in Epi-data and analyzed in SPSS ver. 16. Descriptive statistics were used to present the results that included the computation of frequency and percentages. Bi-variate logistic regression analysis followed by multi variable logistic regression analysis were used for predictor's analysis at 95% confidence interval with odds ratios. The utilization of ANC services was 76.9%, indicating that at least one visit was made. However, the utilization decreased to 43% for those who attended complete set of four or more visits. A majority of deliveries, comprising 62.3%, were assisted by individuals other than skilled health personnel. More than a half didn't know about the government schemes of ANC services and around 13% were never respected on their decision by their husband to seek health care. Adjusted analyses indicated that heard of government schemes of ANC services use (AOR: 6.1, 95% CI: 2.30-16.23) and husband's respect towards their spouse decisions to seek health care (AOR: 8.22, 95% CI: 1.65-40.82) remained significant factors positively influencing ANC services use, while other factors became insignificant after adjustment. These findings suggest that customized interventions focusing on increasing awareness of government schemes on ANC services and promoting respect towards women's decisions could be effective in improving ANC services use among the extremely marginalized Chepang women of Nepal.